2020
DOI: 10.33716/bmedj.760653
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Hematological and Allergic Values in Children with Atopic Dermatitis

Abstract: The Relationship Between Hematological and Allergic Values in Children with Atopic Dermatitis Mehmet Özdin 1 ÖZ Amaç: Bu çalışmada amacımız; Sakarya Üniversitesi Eğitim ve Araştırma Hastanesi (SÜEAH) Pediatrik Dermatoloji Polikliniklerine müracaat eden pediatrik yaş grubunda Atopik Dermatit (AD) hastalarında, periferik kandan ölçülebilen nötrofil lenfosit oranı (NLO), trombosit lenfosit oranı (TLO), eozinofil lenfosit oranı (ELO) ile serum total immün globobülin E (T-IgE) değerleri ve kan eozinofil sayısını te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Neutrophils, lymphocytes, and platelets are important blood parameters that play a role in inflammation. Today, these laboratory parameters are used to evaluate many infectious and inflammatory conditions and are easy to apply and accessible (8). There are data showing that these parameters should be evaluated for the diagnosis and follow-up process of allergic rhinitis as in other allergic diseases (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils, lymphocytes, and platelets are important blood parameters that play a role in inflammation. Today, these laboratory parameters are used to evaluate many infectious and inflammatory conditions and are easy to apply and accessible (8). There are data showing that these parameters should be evaluated for the diagnosis and follow-up process of allergic rhinitis as in other allergic diseases (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In a large sample study conducted in China, house dust mites were reported as the most common allergen, with a rate of 29.7% in children [ 12 ]. In research carried out among asthmatic children in Türkiye, the frequency of house dust mite allergies in preschool and school-age children was reported to be 42.0% and 51.0%, respectively [ 13 ]. In a study conducted in Istanbul, the house dust mite was reported as the most common respiratory allergen in children [ 14 ].…”
Section: Introductionmentioning
confidence: 99%